Biostimulation of Indigenous Microbial Community for Bioremediation of Petroleum Refinery Sludge - Sarkar, Jayeeta; Kazy, Sufia K.; Gupta, Abhishek; Dutta, Avishek; Mohapatra, Balaram; Roy, Ajoy; Bera, Paramita; Mitra, Adinpunya; Sar, Pinaki (Frontiers in Microbiology, 2016)
Nutrient deficiency severely impairs the catabolic activity of indigenous microorganisms in hydrocarbon rich environments (HREs) and limits the rate of intrinsic bioremediation. The present study aimed to characterize the microbial community in refinery waste and evaluate the scope for biostimulation based in situ bioremediation. Samples recovered from the wastewater lagoon of Guwahati refinery revealed a hydrocarbon enriched [high total petroleum hydrocarbon (TPH)], oxygen-, moisture-limited, reducing environment. Intrinsic biodegradation ability of the indigenous microorganisms was enhanced significantly (>80% reduction in TPH by 90 days) with nitrate amendment. Preferred utilization of both higher- (>C30) and middle- chain (C20-30) length hydrocarbons were evident from GC-MS analysis. Denaturing gradient gel electrophoresis (DGGE) and community level physiological profiling (CLPP) analyses indicated distinct shift in community’s composition and metabolic abilities following nitrogen (N) amendment. High throughput deep sequencing of 16S rRNA gene showed that the native community was mainly composed of hydrocarbon degrading, syntrophic, methanogenic, nitrate/iron/sulfur reducing facultative anaerobic bacteria and archaebacteria, affiliated to γ- and δ-Proteobacteria and Euryarchaeota respectively. Genes for aerobic and anaerobic alkane metabolism (alkB and bssA), methanogenesis (mcrA), denitrification (nirS and narG) and N2 fixation (nifH) were detected. Concomitant to hydrocarbon degradation, lowering of dissolve O2 and increase in oxidation-reduction potential (ORP) marked with an enrichment of N2 fixing, nitrate reducing aerobic/facultative anaerobic members [e.g., Azovibrio, Pseudoxanthomonas and Commamonadaceae members] was evident in N amended microcosm. This study highlighted that indigenous community of refinery sludge was intrinsically diverse, yet appreciable rate of in situ bioremediation could be achieved by supplying adequate N sources.